A Univariate Optimization Strategy for Pre-concentration of Cobalt(II) in Various Matrixes by a DLLME before Analysis Using FAAS - Zaman Sahb Mehdi; Saher Abdel Reda Ali Alshamkhawy (Indonesian Journal of Chemistry, 2024)
A procedure based on dispersive liquid-liquid microextraction (DLLME) for cobalt (Co) quantification in an Iraqi environmental matrix by flame atomic absorption spectroscopy (FAAS) was applied in this work. A case-study approach was chosen to obtain further in-depth information on the Co levels and to evaluate the effectiveness of N-salicylideneaniline (SAN) as a complexing agent for pre-concentration and extraction of Co. An univariate strategy was utilized to achieve the optimum extraction conditions. The estimated limits of detection (LOD) and quantification (LOQ) under optimum conditions were 1.04 and 3.47 µg L−1, respectively. The results achieved by the proposed system were compared with those using the microwave digestion/graphite furnace atomic absorption spectrometer (MWD/GF-AAS) for digest samples and also for some water samples (Direct GF-AAS). The proposed procedure was applied for analyzing eleven environmental samples. The detectable Co levels for water samples ranged from 0.72 to 4.30 µg L−1 with a relative standard deviation of 3.7–8.8%, while the concentration for solid samples ranged from 0.17–4.51 µg g−1 (2.4–11.8 RSD %). DLLME/FAAS proposed procedure is effective, simple, and has the benefit of minimizing the organic solvent consumption by a few microliters, which results in little waste.